Locus of Control dan Financial Technology dalam Memoderasi Pengaruh Literasi Keuangan Terhadap Keputusan Investasi - Rafi Faisal, Muhammad; Susilowati, Endah (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to examine the effect of financial literacy on investment decisions and explore the moderating role of locus of control and financial technology among accounting students at UPN Veteran East Java. A quantitative approach was used with a survey method involving 93 respondents, and data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The results of the study indicate that financial literacy has a significant effect on investment decisions, with a T-statistic value of 3.073 and a P-value of 0.002. However, neither locus of control (T-statistic = 0.584; P-value = 0.559) nor financial technology (T-statistic = 0.702; P-value = 0.483) was found to moderate the relationship between financial literacy and investment decisions. The R-square value of 0.728 indicates that 72.8% of the investment decision variables can be explained by this model. These findings emphasize the importance of financial literacy in supporting rational investment decision-making, as well as the need to optimize the role of psychological factors and financial technology in the process.